Deskryptywne i normatywne koncepcje ideologii - Dulęba, Łukasz (Polityka i Społeczeństwo, 2020)
The paper discusses the problem of categorizing the concept of ideology, which in contemporary political theory is returning as a concept with a heavily descriptive meaning. This perspective is the retreat from the more common, but pejorative sense of the ideology as false consciousness. The paper attempts to distinguish the descriptiveness or normativity of meanings of historical concepts of ideology. This critical review is to sensitize researchers in the field of social sciences that the applicability of the concept of ideology relates to the conceptual burden. Analyzing these approaches, the author tries to verify the cognitive meaning of the concept.